2019
DOI: 10.1101/571059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short translational ramp determines efficiency of protein synthesis

Abstract: It is generally assumed that translation efficiency is governed by translation initiation. However, the efficiency of protein synthesis is regulated by multiple factors including tRNA abundance, codon composition, mRNA motifs and amino-acid sequence 1-4 . These factors influence the rate of protein synthesis beyond the initiation phase of translation, typically by modulating the rate of peptide-bond formation and to a lesser extent that of translocation. The slowdown in translation during the early elongation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 56 publications
3
24
0
Order By: Relevance
“…This result is consistent with two recent studies that stressed the importance of the first 10 codons in regulating protein production (Chu et al, 2014;Szavits-Nossan et al, 2018a). Furthermore, the first codons are also experimentally recognised to be critical in determining protein synthesis (Kudla et al, 2009;Bentele et al, 2014;Cambray et al, 2018;Verma et al, 2019). Finally, this result is also consistent with the "slow ramp" hypothesis (Tuller et al, 2010): a ribosome translating the first (slower) codons will be less prone to interfere with other ribosomes downstream the sequence.…”
Section: Discussionsupporting
confidence: 74%
“…This result is consistent with two recent studies that stressed the importance of the first 10 codons in regulating protein production (Chu et al, 2014;Szavits-Nossan et al, 2018a). Furthermore, the first codons are also experimentally recognised to be critical in determining protein synthesis (Kudla et al, 2009;Bentele et al, 2014;Cambray et al, 2018;Verma et al, 2019). Finally, this result is also consistent with the "slow ramp" hypothesis (Tuller et al, 2010): a ribosome translating the first (slower) codons will be less prone to interfere with other ribosomes downstream the sequence.…”
Section: Discussionsupporting
confidence: 74%
“…The strong biases on disfavored DE/P-rich sequences and favored bulky amino acids in the N-terminal regions of bacterial ORFs are in agreement with this assumption (Figure 4 and Figure S4). Many previous studies have pointed out that the sequence features just adjacent to the start codon significantly influence the efficiency of protein biosynthesis (Allert et al, 2010; Goodman et al, 2013; Kudla et al, 2009; Osterman et al, 2020; Salis et al, 2009; Sprengart et al, 1996; Verma et al, 2019). Considering the “bulkiness” of the nascent polypeptide when interpreting the datasets might disclose new landscapes from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our workflows were aided by the use of the high-affinity, 11 amino acid HiBiT tag (87), which is able to complex with a 18 kDa engineered NanoLuc polypeptide (88) and luminesce proportional to the level of HiBiT-tagged protein. We found that this worked well as a C-terminal tag but reduced yields when fused to the N-terminus of sfGFP ( Figure 2 ), perhaps because the HiBiT amino acid sequence is not optimal for early translational elongation (89). Although sfGFP has been optimised to improve folding (90), the minimal size of the HiBiT tag may be less likely to inhibit protein function and accessibility.…”
Section: Discussionmentioning
confidence: 99%